Rancang Bangun Knowledge Management System Politeknik Statistika STIS - Ibnu Santoso; Sanjaya Abdillah Karim (Politeknik Harapan Bersama, 2019)
STIS Polytechnic of Statistics (PS-STIS) is an institutional unit with high work complexity and density. In carrying out its personnel activities, there is no support system that can be used by employees to store and process knowledge related to their work. This may indirectly lead to ineffective and inefficient work in term of costs, time, and other resources. Job-related knowledge is stored in accordance with the decisions of each employee. When needed, knowledge acquisition becomes slow and knowledge is also prone to be scattered or even lost. In this study, we will discuss about design and development of knowledge management system within the scope of PS-STIS. The focus of this research is related to the integration of the system functions to be able to perform knowledge storage, collaboration, and retrieval. The web-based system built applies the basic principles of Knowledge Management System (KMS). it has pages and permissions in accordance with the interests and responsibilities of users. In this research, we used SDLC development method to build the system and evaluated it using blackbox testing method and Survey Usability Scale (SUS). Result of blackbox testing showed that all function performed like expected and SUS score of 74 showed that system built was acceptable to users.